Assessment of thermal, economic, and environmental performance of solar capillary-mat heating systems in hot-summer/coldh-winter zones. Issue 1 (31st December 2022) - Xu, Dengke; Mu, Chaomin; Li, Zhongqing; Zhang, Wenqing
Abstract : To investigate the ability of solar energy to meet building heating requirements in hot-summer/cold-winter zones in China, an experiment was performed with solar capillary mat heating systems (SCHS) from 12/28/2014 to 01/04/2015 in Huainan city. Data from a typical day (Jan. 2) were selected to analyse the dynamic thermal performance, indoor thermal environment, and guaranteed heating time, meanwhile, the economic and environmental benefits of SCHSs were assessed. The results show: (1) The SCHS has good thermal performance, as measured by heat collection efficiency and collection energy; (2) Under the average solar radiation of 420 W/m 2, the solar collectors daily collection energy is approximately 113.08 MJ, and the capillary mats' average heating capacity is 50.9 W/m 2 ; (3) The guaranteed heating time of the SCHS can be up to 14 h a day, indoor air temperatures have a uniform distribution, and the acceptable comfort time (−1.0 < PMV < 0.5) reaches 16 h a day; (4) Compared to energy from electricity, natural gas, or fuel oil, the payback period for solar system investment is 6.3, 11.7, and 6.26 years, respectively, and the SCHSs can reduce CO2 emissions of 1615, 360, and 477 kg/year, respectively. The SCHS can produce environmental and economic benefits.